BRICS space diplomacy and response of non-Western countries: the inscription of Neo-Functionalism (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
Outer space perseveres as a domain of contestation. In fact, the era of the early 2000s was also remarked to be embroiled in a ‘second space race’. In this regard, in November 2019, NATO also declared outer space as its operational domain. In contrast, BRICS formally committed in 2021 to the prevention of an arms race in outer space. Russia and China agreed to cooperate on a permanent manned lunar base and are investing heavily in their space programs. This is ringing bells in Western-led established order. Once the International Space Station (ISS) is decommissioned in 2022, China’s space station, if constructed in 2025, will be the only functioning global space station for which Beijing is already seeking cooperation from partners. Interestingly, NASA’s legislation prevents it from collaborating with the Chinese National Space Agency. This article endeavours to understand the scenario with a two-fold focus: will the emerging countries like BRICS follow the footsteps of the West in militarizing outer space? how countries other than China use this opportunity to attain a desirable position in the international order. The study provides an insight into how non-Western countries have secured a place in attaining a considerable position in outer space.